PEMBENTUKAN KELOMPOK KADER DAN IBU “SAGITA” (Sayang Ibu dan Balita) SEBAGAI UPAYA PENCEGAHAN STUNTING - Kurnia kurnia; Retno Issroviatiningrum (LPPM STIKes ICsada Bojonegoro, 2023)
toddlers. Indonesia, which is a developing country, contributes to the growth in the stunting rate in toddlers in the world where currently Indonesia is ranked fifth in the world's incidence of stunting in toddlers. Stunting can be prevented by community empowerment activities, namely village involvement in detecting and preventing stunting. The purpose of this community service activity is to improve health status by forming a community, especially cadres and mothers who are aware of stunting